Chest physiotherapy and rebound exercise for sputum in patients co-infected with TB and HIV - S. Maharaj; T. Dunpath (AOSIS, 2014)
Patients co-infected with human immunodeficiency virus and tuberculosis find difficulty producing sputum for microscopy culture and sensitivity test.